Variation in winged bean (Psophocarpus tetragonolobus) growth parameters, seed yield, nodulation, and nitrogen fixation (Asian Journal of Agriculture, 2021)
Abstract. Adegboyega TT, Abberton MT, Abdelgadir AH, Mahamadi D, Olaniyi OA, Ofodile S, Babalola OO. 2021. Variation in winged bean (Psophocarpus tetragonolobus) growth parameters, seed yield, nodulation, and nitrogen fixation. Asian J Agric 5: 61-71. Underutilized legumes are widely distributed in tropical agriculture and associated with low yield.  Thus they have not really been fully explored due to lack of research investment, breeding programs targeting crop improvement, marketing, and low awareness of nutritional benefits. This study was conducted to determine the variation in growth parameters, seed yield, nodulation, and nitrogen fixation in winged bean (Psophocarpus tetragonolobus) germplasms. High genotypic and phenotypic coefficients of variances were observed in traits evaluated. The combined analysis of variance for five variables of 25-winged bean accessions showed that replication by year interaction was statistically significant (p ? 0.0001) for nodule parameters and dry shoot weight while it was not significant (p = > 0.05) for dry root weight, and total biomass. Significant variations (p = ? 0.05) were observed among the accessions on some growth parameters. The genetic variability of winged beans could be carefully exploited to provide higher grain yield, as well as other economic and important traits to boost food security and conservation of the plant genetic materials.